Wetland water-management may influence mercury bioaccumulation in songbirds and ducks at a mercury hotspot - Winder, Virginia L (Ecotoxicology (London, England), 2020)
Mercury is a persistent, biomagnifying contaminant that can cause negative behavioral, immunological, and reproductive effects in wildlife and human populations. We examined the role of wetland water-management on mercury bioaccumulation in songbirds and ducks at Kellys Slough National Wildlife Refuge Complex, near Grand Forks, North Dakota USA. We assessed mercury concentrations in blood of wetland-foraging songbirds (80 common yellowthroats [Geothlypis trichas] and 14 Nelson's sparrows [Ammospiza nelsoni]) and eggs of upland-nesting ducks (28 gadwall [Mareca strepera], 19 blue-winged teal [Spatula discors], and 13 northern shoveler [S. clypeta]) across four wetland water-management classifications. Nelson's sparrow blood mercury concentrations were elevated (mean: 1.00 µg/g ww; 95% CL: 0.76-1.31) and similar to those reported 6 years previously. Mercury in songbird blood and duck eggs varied among wetland water-management classifications. Songbirds and ducks had 67% and 49% lower mercury concentrations, respectively, when occupying wetlands that were drawn down with water flow compared to individuals occupying isolated-depressional wetlands with no outflow. Additionally, songbirds within impounded and partially drawn-down wetland units with water flow had mercury concentrations that were 26-28% lower, respectively, than individuals within isolated-depressional wetlands with no outflow. Our results confirm that mercury concentrations in songbirds at Kellys Slough continue to be elevated and suggest that water-management could be an important tool for wetland managers to reduce bioaccumulation of mercury in birds